The prothrombin time/international normalized ratio predicts prognosis in cardiogenic shock - Schupp, Tobias; Behnes, Michael; Rusnak, Jonas; Dudda, Jonas; Forner, Jan; Ruka, Marinela; Egner-Walter, Sascha; Bertsch, Thomas; Müller, Julian; Akın, Ibrahim (Coronary artery disease, 2023)
Objective: The study investigates the prognostic impact of the prothrombin time/international normalized ratio (PT/INR) in patients with cardiogenic shock. Background: Despite ongoing improvements regarding the treatment of cardiogenic shock patients, intensive care unit (ICU)-related mortality in cardiogenic shock patients remains unacceptably high. Limited data regarding the prognostic value of the PT/INR during the course of cardiogenic shock treatment is available. Methods: All consecutive patients with cardiogenic shock from 2019 to 2021 were included at one institution. Laboratory values were collected from the day of disease onset (day 1) and days 2, 3, 4 and 8. The prognostic impact of the PT/INR was tested for 30-day all-cause mortality, as well as the prognostic role of PT/INR changes during course of ICU hospitalization. Statistical analyses included univariable t-test, Spearman’s correlation, Kaplan-Meier analyses, C-Statistics and Cox proportional regression analyses. Results: Two hundred twenty-four cardiogenic shock patients were included with a rate of all-cause mortality at 30 days of 52%. The median PT/INR on day 1 was 1.17. The PT/INR on day 1 was able to discriminate 30-day all-cause mortality in cardiogenic shock patients [area under the curve 0.618; 95% confidence interval (CI), 0.544-0.692; P = 0.002). Patients with PT/INR > 1.17 were associated with an increased risk of 30-day mortality [62% vs. 44%; hazard ratio (HR) = 1.692; 95% CI, 1.174-2.438; P = 0.005], which was still evident after multivariable adjustment (HR = 1.551; 95% CI, 1.043-2.305; P = 0.030). Furthermore, especially patients with an increment of the PT/INR by ≥10% from day 1 to day 2 were associated with an increased risk of 30-day all-cause mortality (64% vs. 42%; log-rank P = 0.014; HR = 1.833; 95% CI, 1.106-3.038; P = 0.019). Conclusion: Baseline PT/INR and an increase of the PT/INR during the course of ICU treatment were associated with the risk of 30-day all-cause mortality in cardiogenic shock patients.
Gesehen am 17.07.2024